2007
DOI: 10.1002/aqc.871
|View full text |Cite
|
Sign up to set email alerts
|

Subtidal macrozoobenthic assemblages along the River Minho estuarine gradient (north‐west Iberian Peninsula)

Abstract: ABSTRACT1. The community composition and spatial distribution of the macrobenthic fauna in relation to abiotic factors was investigated at 20 sites along the River Minho estuarine gradient, in the north-west Iberian Peninsula.2. A total of 68 taxa were identified and the non-indigenous invasive species Corbicula fluminea dominated both numerically (43.1%) and by biomass (97.7%).3. Multivariate analysis identified spatial differences in structure and composition of assemblages and suggests a continuum between f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 58 publications
3
69
2
Order By: Relevance
“…This follows the pattern of most temperate estuaries, and is characterised by having a significant influx of freshwater during the winter, which has an impact on salinity variation (Elliott & McLusky 2002;Chainho et al 2006;Teixeira et al 2008). The presence of gravel at upstream stations and the accumulation of muddy sediments in the stations near of mouth of Cávado estuary detected in the present study has also been observed in other Portuguese estuaries Chainho et al 2007;Sousa et al 2008b;Teixeira et al 2008). …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This follows the pattern of most temperate estuaries, and is characterised by having a significant influx of freshwater during the winter, which has an impact on salinity variation (Elliott & McLusky 2002;Chainho et al 2006;Teixeira et al 2008). The presence of gravel at upstream stations and the accumulation of muddy sediments in the stations near of mouth of Cávado estuary detected in the present study has also been observed in other Portuguese estuaries Chainho et al 2007;Sousa et al 2008b;Teixeira et al 2008). …”
Section: Discussionsupporting
confidence: 88%
“…In general, salinity was lower at most upstream stations (E1, E1a) and higher at most downstream stations (E2, E3 and E3a). Seasonal variations and along to the estuarine gradient as those indicated are very common in Portuguese estuaries (Moreira et al 1993;Azevedo et al 2008;Chainho et al 2008;Sousa et al 2008b;Costa-Dias et al 2010b;Medeiros et al 2012). Winter and spring were the wettest seasons compared to summer, which was generally drier.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…I-Mediterranean endemic; II-Atlantic, present in the Mediterranean; III-Atlantic, absent from the Mediterranean; IV-Atlantic, present in the Mediterranean and Indo-PaciWc Ocean; V-Atlantic, present in the Indo-PaciWc Ocean; VI-Cosmopolitan Fig. 6 Cluster diagram of species present in more than 5% of samples based on the BrayCurtis similarity index (Carvalho et al 2006a;Sousa et al 2007), which is an important food resource for benthic communities (Rodrí-guez-Graña et al 2008). Moreover, the existence of Wner sediments also reXects low levels of physical disturbance.…”
Section: Distribution Of Amphipod Assemblages In Relation To Depthmentioning
confidence: 99%
“…In recent years, several studies have investigated the fauna of the Minho estuary, namely macroinvertebrates (Sousa et al, 2008b), epibenthos (Costa-Dias et al, 2010) and fishes (Antunes and Rodrigues, 2004). However, these studies were mostly focused on the lower estuary, and those regarding fish species were centred on few species (mostly related with professional fishing) and have not considered temporal changes; thus River Minho TFWs are currently poorly known.…”
Section: Introductionmentioning
confidence: 99%